2014
DOI: 10.1038/onc.2014.420
|View full text |Cite
|
Sign up to set email alerts
|

PAX3 and ETS1 synergistically activate MET expression in melanoma cells

Abstract: Melanoma is a highly aggressive disease that is difficult to treat due to rapid tumor growth, apoptotic resistance, and high metastatic potential. The MET tyrosine kinase receptor promotes many of these cellular processes, and while MET is often overexpressed in melanoma, the mechanism driving this overexpression is unknown. Since the MET gene is rarely mutated or amplified in melanoma, MET overexpression may be driven by to increased activation through promoter elements. In this report, we find that transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…A functional study on the role of ETS1 revealed that it exacerbates melanomagenesis through the activation of ETS1-MET axis in combination with or without PAX3. Majority of ETS1 was expressed in cytoplasm while PAX3 is only expressed in nucleus (Kubic 2015). In concordat with this study, Potu et al reported that Ets1 upregulation amplifies NRAS activity via its overexpression which leads to a malignant phenotype.…”
Section: Dusp6 Ets1 and Brn2 Expression In Human Nevi And Thin Melsupporting
confidence: 64%
“…A functional study on the role of ETS1 revealed that it exacerbates melanomagenesis through the activation of ETS1-MET axis in combination with or without PAX3. Majority of ETS1 was expressed in cytoplasm while PAX3 is only expressed in nucleus (Kubic 2015). In concordat with this study, Potu et al reported that Ets1 upregulation amplifies NRAS activity via its overexpression which leads to a malignant phenotype.…”
Section: Dusp6 Ets1 and Brn2 Expression In Human Nevi And Thin Melsupporting
confidence: 64%
“…This finding is supported by Gambarotta et al . (1996) as well as by Kubic et al ., (2015), who both described transcriptional regulation of MET by C‐ets‐1, however, not in a TGFβ1‐dependent context. C‐ets‐1 overexpression has been shown to strongly promote malignant invasiveness of breast cancer cells, which is in line with our findings (Furlan et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma patient specimens, increased MET expression has been implicated in tumor progression, with receptor expression correlating with melanoma growth and metastasis [38,39]. Recent studies have revealed the concomitant overexpression of transcription factors ETS1, PAX3, and SOX10 that drive up-regulation of Met in melanoma cell lines and primary tumors [35,40]. We report herein that increased Met expression mediates the generation of NRAS resistant melanoma in vivo , while inhibition of Met overcomes this resistance, indicating that combination strategies that suppress RTK signaling with MAPK pathway inhibition may be therapeutically beneficial.…”
Section: Discussionmentioning
confidence: 99%